MSME PERFORMANCE IN THE DIGITAL ERA: THEORETICAL STUDY THE ROLE OF LITERACY AND SKILLS - Julianti, Nurul Dewi; Suparno; Nurjanah, Siti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This study uses a theoretical research approach to create proposition regarding the performance of Micro, Small, and Medium Enterprises (MSME) in the digital era. This study elaborates several findings from previous research as a reference. Resource Based View Theory and Human Capital Theory are used as supporting theory. To develop a research reference model that explains the relationship between literacy and abilities and MSMEs' performance in the digital era, qualitative research methods utilizing literature studies were conducted. This study also provides suggestions for developing variables and indicators in measuring performance and other variables that influence MSME performance. The result of the study provide recommendations that literacy and skills as references in the development of Micro, Small, and Medium Enterprises in the digital era have an important role in the performance of MSMEs to improve national economic prosperity.